2002
DOI: 10.21273/horttech.12.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Maturity and Timing of Ethylene Treatment Affect Storage Performance of Green Tomatoes at Chilling and Nonchilling Temperatures

Abstract: Green tomato (Lycopersicon esculentum `Sunny') fruit were stored at 2.5, 5, 7.5, 10, or 12.5 °C (36.5, 41, 45.5, 50, or 54.5 °F) for 1, 3, 5, or 7 days to determine their sensitivity to chilling injury. In subsequent experiments, fruit were treated with ethylene at 20 °C (68 °F) until the breaker stage was reached, either before or after storage at 12.5 °C for 0, 1, 3, 5, or 7 days, or 2.5 °C for 3, 5, 7, or 9 days. Number of days to reach the breaker stage was used as an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…The increase of SSC in nonwaxed fruits stored for 20 days at 5C may be due to the leakage of amino acids, sugars and mineral salts from cells because of cell wall degradation, as suggested by Batu (2003). Chomchalow et al (2002) and Nunes et al (1996) reported that chemical composition was not affected (either by temperature or time exposure) on tomato fruits stored at chilling and non chilling temperatures, while Chiumarelli and Ferreira (2004) applied different waxes on tomato fruit beforestorage at 20C andfound a significant effect on chemical composition only in some kinds of waxes when compared with the control. Figure 3 shows the effect of waxing on chilling injury.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The increase of SSC in nonwaxed fruits stored for 20 days at 5C may be due to the leakage of amino acids, sugars and mineral salts from cells because of cell wall degradation, as suggested by Batu (2003). Chomchalow et al (2002) and Nunes et al (1996) reported that chemical composition was not affected (either by temperature or time exposure) on tomato fruits stored at chilling and non chilling temperatures, while Chiumarelli and Ferreira (2004) applied different waxes on tomato fruit beforestorage at 20C andfound a significant effect on chemical composition only in some kinds of waxes when compared with the control. Figure 3 shows the effect of waxing on chilling injury.…”
Section: Resultsmentioning
confidence: 94%
“…The increase of SSC in nonwaxed fruits stored for 20 days at 5C may be due to the leakage of amino acids, sugars and mineral salts from cells because of cell wall degradation, as suggested by Batu (2003). Chomchalow et al . (2002) and Nunes et al .…”
Section: Resultsmentioning
confidence: 99%
“…4(E)) the differences between breaker fruits at 20 and 6 °C became significant towards the end of storage. Changes in organic acid composition during storage seem to be cultivar dependent, since in standard tomato cvs Sunny26 and Malike23 subjected to chilling temperatures chemical composition was generally unaffected. However, in cv.…”
Section: Resultsmentioning
confidence: 99%
“…Pech et al, 2008). Commercially, ethylene is applied to fresh-market tomatoes harvested at the mature green stage, often at a packinghouse before shipping, to initiate ripening and shorten the ripening time (Chomchalow et al, 2002). Conversely, tomato fruit ripening can be inhibited when fruits are treated with 1-MCP (Guill en et al, 2007;Tassoni et al, 2006).…”
Section: Resultsmentioning
confidence: 99%